Gambaran Kejadian Risiko 4T pada Ibu Hamil di Puskesmas Jatinangor: - Hazairin, Ajeng Maulani; Arsy, Auliya Nurul; Indra, Rosalinda Agnestya; Susanti, Ari Indra (Poltekkes Kemenkes Palu, 2021)
Introduction: High-risk pregnancies are found in pregnant women who are too old, too young, too many, and too close (4T). Many risk factors become screening/early detection of pregnant women in the Poedji Rochjati scorecard, including maternal age <16 years, maternal age >35 years, and mothers who have children 4 or more. Objective: The aim of this study was to describe the 4T risk incidence in pregnant women at the Jatinangor Community Health Center in 2020. Methods: The type of research used was descriptive-analytic with a quantitative approach and cross-sectional design. The population in this study were all pregnant women who were in Jatinangor Health Center. January-September 2020 period, amounting to 2357 people, using accidental sampling technique and obtained a total sample of 149 people. Data analysis using descriptive data analysis with frequency distribution. Results: The results showed that respondents who had the highest risk of 4T were 63.19% at the age of more than 35 years, and multiparity of 43.62%. Conclusion: In this study, it was found that the incidence of 4T risk in pregnant women at the Jatinangor Health Center in 2020 was mostly at the risk of being too old by 58.3% which was dominated by multiparity.